Observations of PAHs in the atmospheres of discs and exoplanets. Issue 1 (25th February 2022) - Ercolano, Barbara; Rab, Christian; Molaverdikhani, Karan; Edwards, Billy; Preibisch, Thomas; Testi, Leonardo; Kamp, Inga; Thi, Wing-Fai
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs) play a key role in the chemical and hydrodynamical evolution of the atmospheres of exoplanets and planet-forming discs. If they can survive the planet formation process, PAHs are likely to be involved in pre-biotic chemical reactions eventually leading to more complex molecules such as amino acids and nucleotides, which form the basis for life as we know it. However, the abundance and specific role of PAHs in these environments is largely unknown due to limitations in sensitivity and range of wavelength of current and previous space-borne facilities. Upcoming infrared space spectroscopy missions, such as Twinkle and Ariel, present a unique opportunity to detect PAHs in the atmospheres of exoplanets and planet-forming discs. In this work, we present synthetic observations based on conservative numerical modelling of typical planet-forming discs and a transiting hot Saturnian planet around solar-type star. Our models show that Twinkle and Ariel might both be able to detect the 3.3 μ m PAH feature within reasonable observing time in discs and transiting planets, assuming that PAHs are present with an abundance of at least one-tenth of the interstellar medium value.